Water quality studies of Semenyih Dam / Masyitah Binti Abdullah - Abdullah, Masyitah (Faculty of Applied Sciences, 2008)
Semenyih Dam is one of the Klang Valley major dams in Malaysia which is an important water resource. Water Quality is important to study because they help us to protect and know the quality of the water that is suitable for human use. The objective of this study is to determine Water Quality Index (WQI), bacteria and metal presence in Semenyih Dam. Water samples from four sampling were sampled from July until August 2008. WQI was calculated based on the six parameters which were Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Total Suspended Solid (TSS) and Ammoniacal-Nitrogen. The findings show that the Water Quality Index (WQI) is in class II. The Class II means that the water needs general treatment to be used as drinking water resource. The amount of bacteria contain in Semenyih Dam is lower than the amounts of standard that are allowed which is 100 bacteria in 100 mL of water sample. The Dam is contaminated with the presence of metal which are lead (Pb), cadmium (Cd) and copper (Cu).